2006
DOI: 10.1002/chin.200651027
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Alkylation of Aldehydes Catalyzed by a Highly Active Titanium Complex of 3‐Substituted Unsymmetric BINOL.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…[23][24][25][26] Recently Harada and Kanda reported that 3-substituted BINOLs exhibited an enhanced catalytic activity compared to 3,3 0 -disubstituted BINOLs in the reaction. 27 Similar phenomena also appeared in our previous research. 28,29 On the basis of this research, a new kind of chiral ligands exhibiting an enhanced asymmetric catalytic activity could possibly be obtained by introducing amino and imino groups into the 3-position of BINOL through the methylene bridge.…”
Section: Introductionsupporting
confidence: 75%
“…[23][24][25][26] Recently Harada and Kanda reported that 3-substituted BINOLs exhibited an enhanced catalytic activity compared to 3,3 0 -disubstituted BINOLs in the reaction. 27 Similar phenomena also appeared in our previous research. 28,29 On the basis of this research, a new kind of chiral ligands exhibiting an enhanced asymmetric catalytic activity could possibly be obtained by introducing amino and imino groups into the 3-position of BINOL through the methylene bridge.…”
Section: Introductionsupporting
confidence: 75%
“…In addition, the same stereochemistry for products derived from addition reactions of organozinc, Grignard, organolithium, organoaluminum, or organotitanium compounds suggests that the catalytic reactions involve acitve species with similar structures which are proposed to be dititanium species I containing one BINOLate ligand and the nucleophile. 11,24,33,36,38 …”
Section: Resultsmentioning
confidence: 98%
“…Therefore, numerous kinds of chiral ligands, such as amino alcohols ( N , O ‐ligands), diamines ( N , N ‐ligands), and diols ( O , O ‐ligands) have been designed and evaluated in the catalytic asymmetric addition of diethylzinc to aldehydes 24–31. As an important O , O ‐ligand, BINOL and its derivatives have been widely studied and earned a prominent status because of their outstanding performance in a good number of asymmetric reactions 32–39…”
Section: Introductionmentioning
confidence: 99%